Efficacy and safety of fondaparinux for the prevention of venous thromboembolism in older acute medical patients: randomised placebo controlled trial. Issue 7537 (26th January 2006) - Cohen, Alexander T; Davidson, Bruce L; Gallus, Alexander S; Lassen, Michael R; Prins, Martin H; Tomkowski, Witold; Turpie, Alexander G G; Egberts, Jan F M; Lensing, Anthonie W A
Abstract: Objective To determine the efficacy and safety of the anticoagulant fondaparinux in older acute medical inpatients at moderate to high risk of venous thromboembolism. Design Double blind randomised placebo controlled trial. Setting 35 centres in eight countries. Participants 849 medical patients aged 60 or more admitted to hospital for congestive heart failure, acute respiratory illness in the presence of chronic lung disease, or acute infectious or inflammatory disease and expected to remain in bed for at least four days. Interventions 2.5 mg fondaparinux or placebo subcutaneously once daily for six to 14 days. Outcome measure The primary efficacy outcome was venous thromboembolism detected by routine bilateral venography along with symptomatic venous thromboembolism up to day 15. Secondary outcomes were bleeding and death. Patients were followed up at one month. Results 425 patients in the fondaparinux group and 414 patients in the placebo group were evaluable for safety analysis (10 were not treated). 644 patients (75.9%) were available for the primary efficacy analysis. Venous thrombembolism was detected in 5.6% (18/321) of patients treated with fondaparinux and 10.5% (34/323) of patients given placebo, a relative risk reduction of 46.7% (95% confidence interval 7.7% to 69.3%). Symptomatic venous thromboembolism occurred in five patients in the placebo group and none in the fondaparinux group (P = 0.029). Major bleeding occurred in one patient (0.2%) in each group. At the end of follow-up, 14 patients in the fondaparinux group (3.3%) and 25 in the placebo group (6.0%) had died. Conclusion Fondaparinux is effective in the prevention of asymptomatic and symptomatic venous thromboembolic events in older acute medical patients. The frequency of major bleeding was similar for both fondaparinux and placebo treated patients.